2018
DOI: 10.1101/373779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey

Abstract: Until the late 20 th Century, it was believed that different sensory modalities were processed by largely independent pathways in the primate cortex, with cross-modal integration only occurring in specialized polysensory areas. This model was challenged by the finding that the peripheral representation of the primary visual cortex (V1) receives monosynaptic connections from areas of the auditory cortex in the macaque. However, auditory projections to V1 have not been reported in other primates. We investigated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 102 publications
(111 reference statements)
6
17
0
Order By: Relevance
“…In agreement with our findings, previous macaque studies have revealed monosynaptic connections between area MT, the equivalent of area hMT+/V5 in primates, and regions in the temporal lobe assumed to be sensitive to auditory motion (28)(29)(30)(31). A recent study further revealed the existence of direct projections from the caudal portions of the middle lateral belt region of the auditory cortex, thought to represent part of the hPT equivalent in macaques (42), to area MT (48). Our suggestion for direct reciprocal projections between hMT+/V5 and hPT is consistent with those findings highlighting the existence of cortical pathways for sensory information exchange at a much lower level of the information processing hierarchy than was previously thought (45,46,49).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our findings, previous macaque studies have revealed monosynaptic connections between area MT, the equivalent of area hMT+/V5 in primates, and regions in the temporal lobe assumed to be sensitive to auditory motion (28)(29)(30)(31). A recent study further revealed the existence of direct projections from the caudal portions of the middle lateral belt region of the auditory cortex, thought to represent part of the hPT equivalent in macaques (42), to area MT (48). Our suggestion for direct reciprocal projections between hMT+/V5 and hPT is consistent with those findings highlighting the existence of cortical pathways for sensory information exchange at a much lower level of the information processing hierarchy than was previously thought (45,46,49).…”
Section: Discussionsupporting
confidence: 90%
“…Animal and human studies have documented auditory influence on cell activities in the primary visual cortex (Brang et al, ; Cappe, Thut, Romei, & Murray, ; Ibrahim et al, ; Meijer et al, ; Murray et al, ; Petro et al, ; Wang, Celebrini, Trotter, & Barone, ). Of note is that auditory influence on the primary visual cortex emerges at short latencies (Cappe et al, ; Raij et al, ; Wang et al, ), even at latencies shorter than those of visual response in a human intracortical EEG recording study (Brang et al, ), suggesting that thalamic nuclei (Cappe, Rouiller, & Barone, ; Henschke et al, ) as well as cortical areas (Falchier et al, ; Ibrahim et al, ; lurilli et al, ; Majka et al, ; Rockland & Ojima, ) mediate auditory influence on the primary visual cortex. Further, the present results, together with the previous finding of sound‐induced modulation of fMRI signals in human LG nucleus (Noesselt et al, ), suggest that the first‐order visual thalamic nucleus could contribute to cross‐modal sensory integration at the early stages of information processing in addition to the higher order visual thalamic nuclei such as the pulvinar and lateral posterior nucleus already known for their multimodal sensitivity (Bonath et al, ; Henschke et al, ; Komura et al, ; Magariños‐Ascone, Buño, & Garcia‐Austt, ; Phillips & Irvine, ; Yirmiya & Hocherman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is that auditory influence is fast, emerging less than 30 ms after the onset of sound, which is shorter than visual response latency (Brang et al, ). Corticocortical connections between auditory and visual areas are considered to mediate the influence (Falchier, Clavagnier, Barone, & Kennedy, ; Henschke, Noesselt, Scheich, & Budinger, ; Ibrahim et al, ; lurilli et al, ; Majka et al, ; Rockland & Ojima, ). Besides, thalamocortical projections, most likely stemming from higher order thalamic nuclei that subserve multimodal sensory processing (Bordi & LeDoux, ; Komura et al, ), are assumed to convey the influence (Henschke et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There may be distinct zones of TPO or its border may be misestimated in ways that complicate interpretation of the injections given the tight anatomical transitions (Supplementary Figure 2). The border between TPO and adjacent areas in the Paxinos et al (2012) atlas has been considered for revision (Majka et al, 2018 Figure 10) and the present gradient of temporal lobe projections follows a path that progresses through and divides the TPO / TE3 region. Another possibility is that the marmoset's default network -A homologue does not have clear differentiation from auditory sensory processing areas.…”
Section: A Default Network Candidate In the Marmosetmentioning
confidence: 99%